An Investıgatıon Of The Self-Perceptıon Levels Of Leadershıp Behavıors Of Sports Scıences Faculty Students - Tan, Çetin; Batmaz, Hüseyin Çağdaş; Zirek, Oğuzhan; Karadağ, Mustafa (METİN YAMAN, 2025)
This study aims to examine the self-perceived levels of leadership behaviors among students of the Faculty of Sport Sciences in relation to various variables. In line with this aim, investigating the relationships between students’ self-perceptions of leadership behaviors and psychological factors such as individual self-confidence, motivation, and social interaction, as well as environmental variables including the educational environment, attitudes of academic staff, and participation in sports activities, will contribute to a more comprehensive understanding of leadership development processes. The research employed a causal-comparative design, and the effects of dependent variables on independent variables were analyzed using comparative statistical tests. The “Leadership Self-Perception Scale,” consisting of four dimensions, was used as the measurement tool and administered to students of Fırat University’s Faculty of Sport Sciences. The data were analyzed using the SPSS 21.0 software package, and depending on the number of groups forming the variables, either t-tests or one-way ANOVA analyses were conducted. The findings indicated that students’ average self-perception scores for leadership behaviors were high in the dimensions of participative, effective, and determined leadership, while they were moderate in the self-confident leadership dimension. The results also revealed that students’ self-perceptions of leadership behaviors varied according to several factors. Furthermore, it was recommended that leadership education programs be developed and customized according to variables such as age, gender, department, and academic year to enhance their effectiveness.

Bu araştırma, spor bilimleri fakültesi öğrencilerinin liderlik davranışlarına yönelik öz algı düzeylerini çeşitli değişkenler açısından incelemeyi amaçlamaktadır. Bu amaç doğrultusunda, spor bilimleri fakültesi öğrencilerinin liderlik davranışlarına ilişkin öz algı düzeylerinin; bireysel özgüven, motivasyon ve sosyal etkileşim gibi psikolojik faktörler ile eğitim ortamı, akademik personelin tutumu ve öğrencilerin spor etkinliklerine katılımı gibi çevresel değişkenler arasındaki ilişkiler açısından incelenmesi, liderlik gelişim süreçlerinin daha bütüncül biçimde anlaşılmasına önemli katkılar sağlayacaktır. Araştırmada model olarak nedensel karşılaştırmalı araştırma modeli kullanılmış ve bağımlı değişkenlerin, bağımsız değişkenler üzerindeki etkisi karşılaştırma testleri kullanılarak ölçülmüştür. Araştırma da ölçme aracı olarak “Liderlik Öz Algısı Ölçeği” kullanılmıştır. Dört boyuttan oluşan ölçek araştırmanın örneklemini oluşturan Fırat Üniversitesi Spor Bilimleri Fakültesi öğrencilerine uygulanmıştır. Veriler SPSS 21.0 paket programıyla analiz edilmiştir. Değişkenleri oluşturan grup sayısına göre de t testi veya tek yönlü varyans analiziyle test edilmiştir. Elde edilen bulgulara göre spor bilimleri fakültesi öğrencilerinin liderlik davranışları öz algı düzeyleri puan ortalamasının katılımcı, etkili ve kararlı lider boyutlarında yüksek düzeyde olduğu; kendine güvenen lider boyutunda ise orta düzeyde bir puan ortalamasının olduğu görülmüştür. Bu araştırmanın sonuçları, öğrencilerin liderlik davranışlarına ilişkin öz algılarının çeşitli faktörlere göre farklılıklar gösterdiğini ortaya koymuştur. Ayrıca liderlik eğitiminin daha etkin olabilmesi için yaş, cinsiyet, bölüm ve sınıf düzeyine göre özelleştirilmiş eğitim programlarının geliştirilmesi de önerilmiştir.
Spor Bilimleri Fakültesi Öğrencilerinin Liderlik Davranışları Öz Algı Düzeyinin İncelenmesi
Keywords: Sports and Recreation; Spor ve Rekreasyon